Dampak Seruan Boikot Umat Muslim terhadap Return Saham Perusahaan Terafiliasi Israel: Sebuah Analisis Event Study - Kamila Maraya Harish; Cupian Cupian (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to analyze the impact of the Muslim boycott call after the issuance of Fatwa MUI No. 83 on the stock returns of Israel-affiliated companies listed on the Indonesia Stock Exchange. The stocks selected for the study include UNVR, FAST, MAPI, MAPA, MAPB, and PZZA. The results of this study indicate that there is no significant difference in the stock returns of companies affiliated with Israel after the issuance of Fatwa MUI No. 83 on November 8, 2023. This finding indicates a delay in the market response to public information related to the boycott call, which is characteristic of markets with lower efficiency levels. This research is expected to provide insights for the public and investors regarding the dynamics of the capital market in Indonesia in responding to a social event. In addition, the results of this study can also be taken into consideration for market authorities and related institutions in evaluating policies aimed at improving capital market efficiency in Indonesia.